Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia - Xu, Yu Mei; Zhao, Zeng Qi; Davies, Kerrie A.; Wang, Jian Ming (Zootaxa, 2017)
This paper describes a new species of Tripylella and gives a new record of Tripyla (family Tripylidae) in Australia, and provides a key to species in the genus Tripylella. Tripylella australis sp. nov. is characterized by having females with a long body (1804–1832 μm), a=41–42, b= 4.4–4.5, c=10.3–11.3, c’=5.4–6.4 and V=51–54%, outer labial setae 13–14 μm long and cephalic setae 3.7–4.5 μm long in one whorl, dorsal tooth posterior to two subventral teeth, tail tapering uniformly, and four single caudal setae on the dorsal part of the tail. Males are similar to females, and have a long body (1870–2014 μm), a=50–55, b= 4.7–4.9, c=11.3–11.4, c’=5.8–6.0 and T=53–56%, horn-shaped spicules, 36–38 μm long, a straight gubernaculum 14–16 μm in length, tail tapering almost uniformly, and four caudal setae on the dorsal part of the tail. A key for identification of Tripylella species is presented. Tripyla setifera Bütschli 1873 is recorded for the first time in Australia, and is re-described.